2019
DOI: 10.1002/mnfr.201801239
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Dietary Polyphenols and Methylxanthines in Normal and Malignant Mammary Tissues from Breast Cancer Patients

Abstract: Scope: Dietary polyphenols may protect against breast cancer. However, it is unknown whether polyphenols reach human malignant breast tumors in molecular forms and(or) at concentrations likely to act against cancer. Methods and Results: Ninteen breast cancer patients consumed three capsules daily from biopsy-confirmed diagnosis to surgery (6 ± 2 days). The capsules contained pomegranate, orange, lemon, olive, cocoa, and grapeseed extracts plus resveratrol, providing 37 different phenolics (473.7 mg), theobromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 40 publications
2
93
0
Order By: Relevance
“…Remarkably, the lack of senescence induction after the treatment with a mixture of RSV metabolites, representative of what is found in malignant mammary tissues, also suggested a potential competition of RSV metabolites for ABC transporters, where each metabolite could present different affinity to these ABC transporters. This fact is essential in the context of among many mechanisms mediating BC resistance, being one of the most studied is the overexpression of efflux ABC transporter proteins that mediates drug resistance .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Remarkably, the lack of senescence induction after the treatment with a mixture of RSV metabolites, representative of what is found in malignant mammary tissues, also suggested a potential competition of RSV metabolites for ABC transporters, where each metabolite could present different affinity to these ABC transporters. This fact is essential in the context of among many mechanisms mediating BC resistance, being one of the most studied is the overexpression of efflux ABC transporter proteins that mediates drug resistance .…”
Section: Discussionmentioning
confidence: 95%
“…[4,11,31] Regarding BC, a recent clinical trial reported the occurrence of RSV-derived metabolites, mainly glucuronidated and(or) sulfated, but not free RSV in both malignant and normal mammary tissues from breast cancer patients who consumed a mixture of dietary polyphenols including RSV. [11] These recently published results support the hypothesis that invokes the RSV metabolites as the putative molecules responsible for the possible in vivo biological effects of RSV against BC. However, another study showed that the conjugation of phenolic metabolites (including those for RSV) prevented short-term in vitro antiproliferative (72 h) or estrogenic/anti-estrogenic activities in BC cells after 3 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations